Spatial and temporal microbial pollution patterns in a tropical estuary during high and low river flow conditions. Issue 2 (30th January 2017) - Wiegner, T.N.; Edens, C.J.; Abaya, L.M.; Carlson, K.M.; Lyon-Colbert, A.; Molloy, S.L.
Abstract: Spatial and temporal patterns of coastal microbial pollution are not well documented. Our study examined these patterns through measurements of fecal indicator bacteria (FIB), nutrients, and physiochemical parameters in Hilo Bay, Hawai'i, during high and low river flow. > 40% of samples tested positive for the human-associated Bacteroides marker, with highest percentages near rivers. Other FIB were also higher near rivers, but only Clostridium perfringens concentrations were related to discharge. During storms, FIB concentrations were three times to an order of magnitude higher, and increased with decreasing salinity and water temperature, and increasing turbidity. These relationships and high spatial resolution data for these parameters were used to create Enterococcus spp. and C. perfringens maps that predicted exceedances with 64% and 95% accuracy, respectively. Mapping microbial pollution patterns and predicting exceedances is a valuable tool that can improve water quality monitoring and aid in visualizing FIB hotspots for management actions. Highlights: Greatest detection of human-associated Bacteroides marker was near rivers. FIB concentrations were highest near rivers and increased during storms. Salinity, temperature, and turbidity were best predictors of FIB concentrations. High spatial resolution FIB maps predicted FIB exceedances with high accuracy.